Motivations to become a professional footballer - Hathairattanakool, Sinthaweechai (Huachiew Chalermprakiet Law Journal, 2024)
Motivation is a process in which a person is stimulated by a stimulus to act or strive to achieve a certain purpose. Whilst several aspire to become professional football players, several youth experience and devote themselves on a journey to become a professional footballer, however, studies suggest that only 180 of the 1.5 million young people across England are able to annually succeed and embark on a career as a professional footballer. The ability for a well-trained youth to prosper in an English Premier League club is only 0.012 percent, which reflects the problems and obstacles of progressing from being an academy footballer to a full-fledged professional footballer. In the context of Thailand, the Professional Sports Promotion Act of 2013 states that professional sports, are sporting disciplines that have organized, systematic competitions according to international standards and provide financial rewards in the form of renumeration or contractual salaries for its athletes. Based on this research, there are two main types of motivation, including physical and social motivation. Furthermore, these types of motivation for athletes can be categorized into internal motivation or external motivation. In addition, it can be seen that motivation and goals in life—achievement motivation—are important factors in learning because achievement motivation is the motivation that makes a person determined to strive to succeed. These motivations and goals are the basis that sport psychology scholars have used as a basic theory for understanding and studying the factors that affect the success of athletes during their emergence as football players. The results from this research suggest together with the motivation to succeed, mental strength is of equal importance. As the study reveals, it is the ability for the athlete to control him/herself, adapt to social situations, ability to solve problems, and most importantly, mental strength helps athletes to control pressure, motivates athletes to push beyond their own physical limits, and helps athletes understand the role of compassion, caring for others and respecting the individual rights of others.